TESTING WEAK-FORM EFFICIENCY FOR THE SAUDI PARALLEL MARKET (NOMU) - Alahmadi, Mazin (International Journal of Accounting & Finance Review, 2023)
Market efficiency is essential for a thriving stock exchange and has a substantial impact on capital investments, particularly in emerging markets. This article examines the weak-form efficiency of Nomu, the Saudi Arabian parallel stock exchange. The study employed various statistical tests on the collected closing values of the Nomu index from May 1, 2019, to May 31, 2023. The return normality and stationarity were investigated using the Jarque-Bera, Augmented Dickey-Fuller (ADF), and Phillips-Perron (PP) tests. The Variance Ratio (VR) test was used to assess autocorrelation, while the Wald-Wolfowitz Runs (WWR) test was utilized to examine random walk behavior. While the Runs test indicated some randomness, all other tests rejected their null hypotheses, indicating that the Nomu market is inefficient according to the weak-form model. This inefficiency suggests that historical trading data may predict future prices, which could discourage foreign capital inflows, thereby limiting Nomu's growth and investment appeal. The significance of these findings for regulators and policymakers in formulating market regulations and policies aimed at enhancing Nomu's efficiency and investor appeal cannot be overstated. This paper, with its robust methodology, is believed to be the first to evaluate the Nomu market's weak-form efficiency since its inception, contributing to a better understanding of market dynamics in emerging stock exchanges.JEL Classification Codes: C12, G14, F21.